Anaerobic co‐digestion of food waste and microalgae in an integrated treatment plant. Issue 6 (15th September 2021) - Ferreira, Luísa Ornelas; Astals, Sergi; Passos, Fabiana
Abstract: BACKGROUND: Anaerobic co‐digestion has been considered for improving anaerobic digesters' stability and methane production, particularly for residues with low biodegradability or lack of alkalinity. Food waste was identified as a biomass with macro and micronutrients unbalance and low alkalinity content, both of which hamper its anaerobic digestion. The present study focused on evaluating the anaerobic co‐digestion of food waste and microalgal biomass harvested from an open pond treating food waste digestate. RESULTS: According to BMP tests results, mono‐digestion of food waste showed low methane yield (~35–68 mL CH4 ·g VS −1 ), most likely due to acid accumulation, as was observed by the low pH and low methane content in biogas. Process stabilisation was further attested through anaerobic co‐digestion with microalgae at different proportions in terms of volatile solids ( VS ). The highest methane yield was obtained at 75:25 of food waste and microalgae (514 mL CH4 ·g VS −1 ), with the highest synergy between substrates (28% higher compared to theoretical value). Moreover, estimates for real scenarios of co‐digestion in an integrated treatment system composed of an anaerobic reactor and microalgae‐based ponds revealed that, due to low microalgae production, proportions of 99:1 would be more realistic. CONCLUSION: Research showed how a higher proportion of food waste was preferable, although a minimum amount of microalgae seemed important for maintaining process stability and increasing methane production. In the demonstration‐scale plant, co‐digestion and co‐disposal was estimated to be more sustainable when carried out in solid‐state or with recirculation of treated effluent. © 2021 Society of Chemical Industry (SCI).